(untitled) (UNED Research Journal, 2018)
Birds are the main seed dispersers in neotropical ecosystems and it is important to understand their role in the natural regeneration of degraded environments. Here, we analyze dispersion by resident birds in two remnants of riverine forest in the urban watershed of the Torres river, San José, Costa Rica. We visited the sites four times per season, in dry, rainy and transition periods. On each visit we set up standard-size mist nets to capture birds, collect their excreta and extract seeds. In total we captured 168 birds from 23 resident species (12 families, five orders). We captured more individuals and species in Dry-Rainy transition, without difference among sites. The Dry-Rainy transition had more total seeds; higher seed capture rate, and a higher seed mean per bird. Resident birds can adapt to different scenarios and their role in seed dispersion should be promoted in urban ecosystems.